PENGARUH HARI PERDAGANGAN PADA ABNORMAL RETURN DAN VOLATILITAS RETURN SAHAM INDEKS LQ45 - Handayani, Putu Sukma; Suartana, I Wayan (E-Jurnal Akuntansi, 2015)
Efficient Market Hypothesis explains that investors are not allowed to make price forecasts and stock returns using past stock prices. Several studies have found that contrary to the Efficient Market Hypothesis, this deviation is called market anomalies. Anomalies caused structured market movements at a given time so that investors can predict return movement patterns. One of the market anomalies is effect of the trading day (day of the week effect).The aim of this study was to investigate the existence of day of the week effect to determine the effect of the trading day on abnormal return and volatility of stock returns LQ45 in Indonesia Stock Exchange. The samples were 35 stocks listed in LQ45 from January to December in 2013 that obtained by purposive sampling method. The analysis method was multiple linear regression with dummy variables.The findings indicate that there is a day of  week effect on abnormal return and volatility of stock returns. Tuesday has the lowest abnormal return and Wednesday has the hisgest abnormal return on. Volatility of stock return is highest on Wednesday and lowest on Fridays.
Keywords: efficient market hypothesis, the effect of the trading day, abnormal return, volatility of stock returns.